The effect of weld groove variations on the impact toughness and hardness of AISI 1050 steel - Iqbal, Maulana; Azwinur, Azwinur; Ibrahim, Akhyar (Politeknik Negeri Lhokseumawe, 2025)
Shielded Metal Arc Welding (SMAW) is a metal joining process that utilizes heat energy to melt both the base metal and the electrode. This study aims to evaluate the effect of weld groove variations on the impact toughness and hardness of AISI 1050 steel. Three types of groove configurations were examined: V Groove, Bevel Groove, and Double V Groove. Tests were conducted in the regions of the Weld Metal, Weld Root, Heat-Affected Zone (HAZ), and Base Metal using a welding current of 100 Amperes. The test results show that the Bevel Groove produced the highest impact toughness at the Weld Root (1.78 Joule/mm²), the V Groove at the Weld Metal (1.65 Joule/mm²), and the Double V Groove at the HAZ (1.48 Joule/mm²). In terms of hardness, the V Groove and Double V Groove showed the highest values in the HAZ (86.5 HRC), while the Bevel Groove exhibited the highest hardness in the Base Metal (81 HRC). The lowest hardness value was found in the Weld Root of the Bevel Groove (56.67 HRC). Overall, the hardness values in the Weld Metal area for all three groove types were the same, measuring 76.5 HRC